A comparison study between morphological, anatomical and some elements in Mentha piperita and Ocimum basilicum (Al-Mukhtar Journal of Basic Sciences, 2025)
In this study, morphological and anatomical findings were studied. The two species showed great variation in phenotypic traits such as habit; Mentha piperita L is herbaceous, while Ocimum basilicum L is a shrubby plant. Blade length was 3.18 cm and 6.4 cm in M. piperita L  and O. basilicum L. respectivly. The leaves are simple in shape, oval in O. basilicum L and the blade with a serrated edge is whole and compound in M. piperita L . The color of the leaves was dark green in M. piperita L while in O. basilicum L it was light green. The length of the roots of M. piperita L (21.6 cm), O. basilicum L (8.76 cm). The color of the flower is white in O. basilicum L and white to purplish in M. piperita L. On the fresh stems and roots of both species, they show their similarities and differences. Both species have square stems, and a cortex, epidermis, xylem, phloem, and phloem are found in the stem, as well as angular tissue cells in the cortex. However, Collenchyma tissues are spread more or less uniformly at the four corners of the stem in M. piperita L, in contrast to O. basilicum L which is spread all over the stem. The cortex in the femoral M. piperita is wide, and this is due to the presence of vacuole parenchyma tissue. The presence of stomata tissues in mint is due to the fact that the plants originate from soils that are waterlogged or partially submerged in water. The amounts of potassium in O. basilicum L and M. piperita L were variable, respectively (4.46) (4.01). Sodium, calcium, and phosphorous were found in M. piperita L (0.03, 1.53 and 0.59), and in O. basilicum L (0.56, 2.67 and 0.46) respectively. For phytochemicals, M. piperita L  and O. basilicum L were similar in the presence or absence of secondary metabolites, except tannin is present in M. piperita L